Geography of Solidarity: Spatial and Temporal Patterns. (2016) - Emadi, Noora Al; Leson, Heather; Lucas, Ji; Meier, Patrick; Borge-Holthoefer, Javier
Abstract: Crowdsourcing technologies represent a paradigm shift in the way certain tasks are performed. Linux, Wikipedia or OpenStreetMap represent massive achievements that are changing our access to open software technology, knowledge and geoservices. These changes have also reached humanitarian response in front of man-made or natural disasters: digital humanitarians (DH) are given the chance to remotely help out those in urgent need, by accomplishing thousands of microtasks that augment the information about the disaster for those who work on the ground. However, the organisers and designers of these complex technological platforms need also to consider how to achieve larger, better, faster humanitarian reaction; as well as how to build, expand and maintain a volunteer community. This paper studies the temporal and geographical patterns of past online humanitarian response, and attempts to find clues that optimize the potentialities of a DH platform. Our findings suggest that the volunteers are strongly committed to the tasks: their contributions are submitted at a very fast pace, and they contribute repeatedly over time; also, such contribution is heavily driven by mass media coverage of the disaster: an increase in the media coverage is closely followed by an increase in the volunteers response. On the geographic side, there are large asymmetries regarding the origin of contributions, with a clear skew towards English-speaking areas. All these analysis outcomes inform us about human activity temporal and temporal patterns in very specific, unexplored context –time-constrained task accomplishing; additionally, such outcomes should rigorously inform future humanitarian technologies, and associated activities.